2021
DOI: 10.1128/aac.02552-20
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fluconazole Administration on Gut Microbiome, Intestinal Barrier, and Immune Response in Mice

Abstract: Antibiotics which can treat or prevent infectious diseases play an important role in medical therapy. However, the use of antibiotics has potential negative effects on the health of the host. For example, antibiotics use may affect the host's immune system by altering the gut microbiota. Therefore, the aim of the study was to investigate the influence of antifungal (fluconazole) treatment on gut microbiota and immune system of mice. Results showed that gut microbial composition of mice receiving fluconazole tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 29 publications
0
19
3
Order By: Relevance
“…Phylum Patescibacteria appeared to be among the most affected phylum in the murine gut during amoxicillin treatment since a significant reduction was detected during treatment in group D ( Fig 4 ). A reduction of Patescibacteria has previously been demonstrated during treatment with the antifungal compound fluconazole [ 69 ] and it has also been demonstrated as highly sensitive to inorganic contamination in drinking water [ 70 ]. However, little information regarding the potential health related effects of these bacterial phyla in the gut is found.…”
Section: Discussionmentioning
confidence: 99%
“…Phylum Patescibacteria appeared to be among the most affected phylum in the murine gut during amoxicillin treatment since a significant reduction was detected during treatment in group D ( Fig 4 ). A reduction of Patescibacteria has previously been demonstrated during treatment with the antifungal compound fluconazole [ 69 ] and it has also been demonstrated as highly sensitive to inorganic contamination in drinking water [ 70 ]. However, little information regarding the potential health related effects of these bacterial phyla in the gut is found.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, miconazole is a broad-spectrum azole antifungal against candidiasis, with some activity against Gram-positive bacteria as well [ 17 ]. There are few reports of antifungal drugs affecting intestinal mucosal morphology, gut microbiota and immunity [ 36 ]. Therefore, further studies are needed to evaluate the influence of the antifungal miconazole on the gut microbiota and immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Fungal infections can occur in oncology patients due to decreased immunity and often require the use of systemic antifungal agents. While many studies have examined the impact of antibiotic use on the GIT microbiome far fewer have examined antifungal use on the microbiome, with most using mouse models ( Qiu et al., 2015 ; Sam et al., 2017 ; Udawatte et al., 2020 ; Heng et al., 2021 ). Past mouse studies looking at antifungal use identified Bacteroides , Alistipes , Lactobacillus , some Firmicutes, and Proteobacteria taxa to be increased while members of the Clostridium XIVa were decreased ( Qiu et al., 2015 ; Udawatte et al., 2020 ; Heng et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have examined the impact of antibiotic use on the GIT microbiome far fewer have examined antifungal use on the microbiome, with most using mouse models ( Qiu et al., 2015 ; Sam et al., 2017 ; Udawatte et al., 2020 ; Heng et al., 2021 ). Past mouse studies looking at antifungal use identified Bacteroides , Alistipes , Lactobacillus , some Firmicutes, and Proteobacteria taxa to be increased while members of the Clostridium XIVa were decreased ( Qiu et al., 2015 ; Udawatte et al., 2020 ; Heng et al., 2021 ). We however identified significantly decreased Bacteroidetes taxa ( Bacteroides , Parabacteroides , and Alistipes ) as well as Lachnospiraceae, and Ruminococcaceae, including butyrogenic ( Faecalibacterium, Subdoligranulum , and Anaerostipes ), and acetogenic taxa ( Blautia ) among patients treated with antifungals.…”
Section: Discussionmentioning
confidence: 99%